(untitled) (Journal of Academic Research, 2022)
This paper aims to investigate the effect of temperature of process annealing heat treatment on some tensile properties and microstructure of cold-rolled 1010 steel. The cold-rolled sheet was cut into the standard tensile test specimens and then the samples were annealed at 300, 400, 500, 550, 600, and 650oC. Tensile and microscopic tests were conducted on the samples. Process annealing temperatures had a significant effect on properties and microstructure. Yield and Ultimate tensile strengths decreased massively from 638 and 662 MPa of the cold rolled steel to 169 and 309 MPa respectively of the treated samples at 650oC. On the other hand, percent elongation improved noticeably from 2 to 35 percent. The microstructure showed a formation of a new set of free-strain grains, that is, the recrystallization temperature, starting at 600oC and finishing at 650oC. This range was of the transition from brittle to ductile fracture. The dominant microstructure was ferrite and pearlite, with elongated grains before 600oC and recrystallized grains at 600oC and above.